2010
DOI: 10.2353/ajpath.2010.090812
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 as a Prognostic Marker for Glioma Progression and Patient Survival

Abstract: Accumulating evidence indicates that miRNA expression can be used as a diagnostic and prognostic marker for human cancers. We report that the expression level of miR-182 was markedly up-regulated in glioma cell lines and in human primary glioma specimens. Quantitative PCR analysis showed that miR-182 was significantly increased by up to 32-fold in glioma tumors compared with the adjacent nontumor brain tissues obtained from the same patient. Elevated expression of miR-182 was further identified by in situ hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 42 publications
8
106
0
4
Order By: Relevance
“…Our previous microarray analysis showed that miR-486 is substantially overexpressed in gliomas [28]. Consistently, real-time PCR analysis revealed that miR-486 was markedly overexpressed in 8 primary glioma tissues compared with the paired tumor-adjacent brain tissues, as well as in all 14 tested glioma cell lines compared with NHA ( Figure 5A and 5B).…”
Section: Mir-486 Overexpression Correlates With Progression Of Human supporting
confidence: 52%
See 1 more Smart Citation
“…Our previous microarray analysis showed that miR-486 is substantially overexpressed in gliomas [28]. Consistently, real-time PCR analysis revealed that miR-486 was markedly overexpressed in 8 primary glioma tissues compared with the paired tumor-adjacent brain tissues, as well as in all 14 tested glioma cell lines compared with NHA ( Figure 5A and 5B).…”
Section: Mir-486 Overexpression Correlates With Progression Of Human supporting
confidence: 52%
“…Analysis using publicly available algorithms (TargetScan, Pictar, miRANDA) showed that Cezanne is the predicted target of miR-486 (Figure 2A), a miRNA that has been found to be substantially overexpressed in gliomas [28]. To investigate the effect of miR-486 on Cezanne expression and its biological role in gliomas progression, U87MG and SNB19 glioma cells were engineered to stably overexpress miR-486 ( Figure 2B).…”
Section: Mir-486 Targets and Suppresses Cezannementioning
confidence: 99%
“…In addition to our human tissue studies showing that miR-182 is upregulated in a subset of malignant melanomas (Segura et al, 2009), this miRNA has also been found to be a prognostic marker for glioma progression (Jiang et al, 2010), and to be highly expressed in colon (Bandres et al, 2007) and breast cancer cell lines (Guttilla and White, 2009). Therefore, anti-miR-182 may have additional antitumoral applications beyond melanoma.…”
Section: Targeting Liver Metastasis With Anti-mir-182mentioning
confidence: 58%
“…The signature included three miRNAs (miR‐20a, miR‐106a, and miR‐17‐5p) that were protective and seven (miR‐31, miR‐222, miR‐148a, miR‐221, miR‐146b, miR‐200b, and miR‐193a) that were risky with respect to the association between their expression and patient survival. Additionally, other studies have found that high expression of miR‐21, miR‐182, and miR‐196 as well as low expression of miR‐181b and miR‐106a are associated with poor patient outcomes 19, 85, 86.…”
Section: Introductionmentioning
confidence: 97%
“…18 identified 12 miRNAs (miR‐9, miR‐15a, miR‐16, miR‐17, miR‐19a, miR‐20a, miR‐21, miR‐25, miR‐28, miR‐130b, miR‐140, and miR‐210) that were upregulated and two (miR‐184 and miR‐328) that were downregulated during progression 18. Other studies have additionally found miRNAs that are differentially expressed in advanced clinical stages of GBM, including miR‐182, which is upregulated and miR‐137, which is downregulated in late stages 19, 20.…”
Section: Introductionmentioning
confidence: 99%